2020
DOI: 10.1186/s40816-020-00235-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the nutritional value and antioxidant activities of common Bangladeshi edible mushrooms

Abstract: Background Mushrooms have been recognized both as medicine and nutritional food in many countries for thousands of years, owing to the presence of significant amounts of carbohydrates, proteins, lipids, fibers, and antioxidants. This study aims at evaluating the nutritional contents and antioxidant potentials of seven types of mushrooms cultivated in Bangladesh. Methods Proximate composition analysis of the collected mushrooms was performed to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
3
9
0
1
Order By: Relevance
“…This phenomenon also appeared in that of yeast [ 49 ]; for example, Xyl and Ara existed in different yeast species. Our results showed that the types of sugar in tested samples were in agreement with previous results [ 50 ]. Currently, sugar might play an important role in food and provide the majority of energy for human being.…”
Section: Resultssupporting
confidence: 93%
“…This phenomenon also appeared in that of yeast [ 49 ]; for example, Xyl and Ara existed in different yeast species. Our results showed that the types of sugar in tested samples were in agreement with previous results [ 50 ]. Currently, sugar might play an important role in food and provide the majority of energy for human being.…”
Section: Resultssupporting
confidence: 93%
“…Studies concerning the exploitation of mushrooms have been done before [17,26], but are still considered unsatisfactory [9] and scarce [15]. Even though they have been well known in the past to have many benefits especially as a food source, medicine and a source of income through trading [1][2][3]7,11,14,[20][21][22]27,28]. A number of efforts to identify macroscopic mushrooms has been done in Indonesia, 30 types of mushrooms has been identified in Rumbio Sacred forest, Riau [15]; 34 Types of mushroom has even been identified in Halimun Salak Mountain National Park in Lebak Regency, Banten [16] 14 types of mushrooms in Mbeji Wonosalam Forrest on the slope of Anjasmoro Mountain [29]; 20 types of mushrooms in Mekarsari tourist park [30] and 18 types of mushrooms in Bayur forest, West Kalimantan [31].…”
Section: Types Of Edible Forest Mushroomsmentioning
confidence: 99%
“…Mushrooms have been known for thousands of years throughout the world, as nutritious food and for treatment [1][2][3]. The Ancient Greeks believed that mushrooms gave warriors strength in battle, and the Romans regarded mushrooms as "Food of the Gods."…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, people are more concerned about their diet [13] and fitness [14]. Presently, oyster mushrooms are appreciated as food not only for their texture and flavor [3] but also for their chemical, nutritional characteristics, and medicinal properties [15] and health benefits [16]. Due to their taste, flavor, high nutritional values, and medicinal properties, nowadays P. ostreatus is the most popular and consumed mushroom [17] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%